The acculturation process of old Mrs. Pan reflected in Pearl S Buckâ€™s The Good Deed - Praptawati, Destary; Ariyani, Nevita Rizki (EduLite: Journal of English Education, Literature and Culture, 2023)
Diaspora still becomes one of the big issues in sociological aspect. Acculturation has been relevant to the topic of diaspora. The issue raised in this study is acculturation process which is experienced by people who do migration by leaving their homeland to a new country caused by any condition happens in their homeland. This study attempts to analyze the acculturation process experienced by old Mrs. Pan in Pearl S Buckâ€™s short story â€œThe Good Deedâ€. This study applied descriptive qualitative method and several steps used in organizing the data; reading the short story, identifying the data, classifying the data, reducing the data, analyzing the data and finally the data analysis presented in descriptive form. In conducting this study, primary data and secondary data were used. The primary data were taken from The Good Deed short story by Pearl S. Buck published in 1953 and the secondary data were taken from journals, e-journals, books, e-books. In conclusion, this study found that acculturation process reflected in old Mrs. Pan as the main character. She experienced the acculturation process as she moved to America because of the conflict which happened in China. She faced the acculturation process in her movement to the new country such as acculturative stress and separation as one of acculturationâ€™s strategy she encountered.